Peroxisome proliferator-activated receptor-γ gene polymorphism in psoriasis and its relation to obesity, metabolic syndrome, and narrowband ultraviolet B response: A case-control study in Egyptian patients - Iman Seleit; Ola Ahmed Bakry; Eman Abd El Gayed; Mai Ghanem (Wolters Kluwer Medknow Publications, 2019)
Background: Psoriasis is a common dermatologic disease with multifactorial etiology in which genetic factors play a major role. Peroxisome proliferator-activated receptor (PPAR)-γ is expressed in keratinocytes and is known to affect cell maturation and differentiation in addition to its role in inflammation. Aim: To study the association between PPAR-γ gene polymorphism and psoriasis vulgaris in Egyptian patients to explore if this polymorphism influenced disease risk or clinical presentation. Methods: Forty-five patients with psoriasis vulgaris and 45 age, sex and body mass index matched healthy volunteers who have no present, past or family history of psoriasis as a control group were enrolled. Selected cases included obese and nonobese participants. Detection of PPAR-γ gene polymorphism was done with restriction fragment length polymorphism polymerase chain reaction. Narrow-band ultraviolet B (NBUVB) was given for every case three times/week for 12 weeks. Results: Homopolymorphism, heteropolymorphism, and Ala allele were significantly associated with cases (P = 0.01, P = 0.01, and P = 0.004, respectively) and increased risk of occurrence of psoriasis by 5.25, 3.65, and 3.37 folds, respectively. Heteropolymorphism was significantly associated with nonobese cases compared to obese ones (P = 0.01). Ala allele was significantly associated with obese cases (P = 0.001) and increased risk of occurrence of psoriasis in obese participants by 1.14 folds. Homopolymorphism, heteropolymorphism, and Ala allele were more prevalent among obese cases without metabolic syndrome (MS) than obese cases with MS but without statistical significance. Percentage of decrease of mean Psoriasis Area and Severity Index score before and after 3 months of treatment with NBUVB was higher in cases with heteropolymorphism with no significant difference between homo- and heteropolymorphism. Conclusion: PPAR-γ gene polymorphism is associated with and increased the risk of psoriasis and its associated obesity in Egyptian patients. It has no role in NBUVB response in those patients. Future large-scale studies on different populations are recommended.